Prinsip Kerjasama dalam Film Kartun Avatar - Yuli Tiarina (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
This study is aimed at analyzing the implementation of the cooperative principles in Avatar cartoon movie.  It was a descriptive study with the content analysis technique. The data were taken from the conversation from the characters in   the Avatar movie. The utterances were grouped into four types of cooperative principles; they are the maxim of quantity, the maxim of quality, the maxim of relation and the maxim of manner. It was found that the utterances among the characters in Avatar cartoon movies both fulfill and violate the cooperative principles. Key words: utterances, conversation, cooperative principles